1984
DOI: 10.1055/s-2008-1052339
|View full text |Cite
|
Sign up to set email alerts
|

The Wiedemann-Rautenstrauch or Neonatal Progeroid Syndrome - Neuropathological Study of a Case

Abstract: Neuropathological data from the autopsy of a 5 1/2 year-old female patient with the Wiedemann-Rautenstrauch or neonatal progeroid syndrome are reported. Extensive demyelination is found in the central nervous system with occasionally a tigroid pattern and with large amounts of neutral fats and intermediate debris of myelin breakdown in macrophages. These lesions are characteristic of pure sudanophilic leucodystrophy. Features differentiating the findings from those in Pelizaeus-Merzbacher disease and in other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…One of our patients died of bronchopneumonia. Because no pathological details were obtained in these patients, we cannot comment on the neuropathological findings of sudanophilic leucodystrophy reported by Martin et al 12 Radiographs of our three patients showed skeletal abnormalities that have been previously described6 (table 2). In addition, our patient 3 had a high mandibular angle and bone age in agreement with his chronological age.…”
Section: Discussionmentioning
confidence: 55%
“…One of our patients died of bronchopneumonia. Because no pathological details were obtained in these patients, we cannot comment on the neuropathological findings of sudanophilic leucodystrophy reported by Martin et al 12 Radiographs of our three patients showed skeletal abnormalities that have been previously described6 (table 2). In addition, our patient 3 had a high mandibular angle and bone age in agreement with his chronological age.…”
Section: Discussionmentioning
confidence: 55%
“…This is associated with a spectrum of clinical features, including delayed psychomotor development and physical growth, alopecia, macrocephaly and lipoatrophy (Arboleda et al 1997;Bitoun et al 1995;Castineyra et al 1992;Devos et al 1981;Martin et al 1984;Pivnick et al 2000;Toriello 1990). No genomic DNA mutations have yet been reported in WRS, but because lipodystrophy is a central feature, genes that cause lipodystrophy can be considered as candidates.…”
Section: Introductionmentioning
confidence: 99%
“…The patient died at 5 1/2 years of age. Her neuropathological data were presented in a separate paper, which indicated an extensive demyelination of the central nervous system (Martin and Ceuterick, 1984). The clinical features common to these five patients and the patient we described included progeroid face apparent from birth, generalized diminution of the subcutaneous fat, growth and developmental delay, hydrocephaloid skull, persistent fontanel, prominent scalp veins, sparse scalp hair, hypoplastic faciat bones, high nasal bridge and large penis.…”
Section: Discussionmentioning
confidence: 70%